A Web-Based Management Information System for Human Resources in Selected Universities of Duhok Province - Haji, Vaman M.; Ahmed, Nawzat S. (Science Journal of University of Zakho, 2017)
Today, all managers use the information system to manage their organization efficiently and effectively. Moreover, a management information system (MIS) is a type of computerized information systems. Hence, human resource management information system (HRMIS) has a fast processing to produce accurate information within the organization environment. Therefore, many researchers proposed numerous HRMISs for university campuses. However, some universities, including Kurdistan Region universities are still relying paper-based system in managing their human resources. Based on that, this study aims to identify and analyze current systems which are used for managing and accessing human resource information in the university campus. Further, the study tries to design a web-based HRMIS based on the requirements achieved from aforementioned aim. The data collection of this study has been carried out at three universities, as a case study, in Duhok province. A mixed method of data collection was done. Then, the qualitative method of data collection conducted using interviews and observation instruments. Also, the quantitative method conducted using system usability scale (SUS) to evaluate the designed web-based HRMIS. Further, the analysis of collected data was based on the strategic planning technique using SWOT (Strengths, Weaknesses, Opportunities and Threats) to identify strengths, weaknesses, opportunities and threats points. Then, the requirements of designing a proposed web-based HRMIS were achieved. After implementing of the proposed system, the evaluation results of SUS were conducted to be acceptable (i.e. total score is 72.03%) based on the end-user viewpoints. Further, the reliability of the proposed HRMIS will be conducted at the University by using reliability measurement tools after implementing such system for a period of time.
Keywords: Human Resource Management Information System; SWOT; System Usability Scale; Duhok